High compliance with guideline recommendations but low completion rates of adjuvant chemotherapy in resected pancreatic cancer: a cohort study - Weinrich, Malte; Weiß, Christel (Annals of medicine and surgery, 2018)
Background: Adjuvant chemotherapy (adCx) is an integral part of multimodal treatment in resected pancreatic ductal adenocarcinoma (PDAC) and is recommended by the German S3 guideline since 2007 in all patients. We aimed to investigate the impact of this guideline at our institution. - Methods: In 151 of 403 pancreatic resections performed histopathology revealed PDAC. Follow-up data were available from 143 patients (95%) representing our study group. The rate of recommended, initiated and fully completed adCx was analyzed for period 1 (09/2003-07/2007) and period 2 (08/2007-08/2014). - Results: Our study group comprised 49 patients in period 1 and 94 patients in period 2. AdCx was recommended, initiated and completed in 42/49 (86%), 34/49 (69%) and 22/49 (45%) patients in period 1 and in 93/94 (99%), 78/94 (83%) and 49/94 (52%) patients in period 2, respectively. Only the increase in recommendations for adCx was statistically significant (p=0.0024). Overall, only 50% (71/143) of patients fully completed the Cx protocol. Completed adCx resulted in a significantly longer (p=0.0225) overall survival compared to patients with incomplete or without adCx. Multiple logistic regression revealed adCx (p=0.0046) as independent factor of survival. The hazard ratio for fully completed adCx was 0.406 and for incomplete adCx 0.567. - Conclusion: Our results indicate a high acceptance of the S3-guidline recommendation for adCx in resected PDAC in a routine setting, which, however, is completed in only 50% of all patients. Fully completed adCx had the most powerful effect on improving overall survival.